Bridging the proficiency gap: A needs analysis of Indonesian maritime cadets’ speaking skills for ESP course design - Dhinar Sari; Nur Hidayanto Pancoro Setyo PutroNur Hidayanto Pancoro Setyo Putro (Universitas Islam Negeri Ar-Raniry, 2026)
This study aims to identify the speaking skills needs of maritime cadets by examining target needs, learning needs, and the discrepancies between current instructional practices and the communicative demands of the maritime industry. A needs analysis approach was employed within the English for Specific Purposes (ESP) framework, utilizing a mixed-methods design. Quantitative data were collected through a questionnaire administered to maritime cadets, while qualitative data were gathered via semi-structured interviews with two Maritime English lecturers. The findings indicate that the majority of cadets demonstrate only a basic level of speaking proficiency, whereas the expected level for effective maritime communication is at least intermediate. Key communicative situations requiring English speaking skills include giving instructions and commands on board, as well as engaging in social interactions among crew members. Regarding learning needs, cadets show a preference for interactive speaking activities, including simulations, role-plays, presentations, and pair discussions. Nevertheless, several obstacles persist, such as limited vocabulary, pronunciation difficulties, low self-confidence, and insufficient opportunities for speaking practice. The study further identifies multiple learning gaps, including disparities in proficiency levels, limited speaking practice, inconsistencies in instructional delivery, and a lack of digital media specifically designed to support speaking practice in maritime contexts.